Molecular link between auxin and ROS-mediated polar growth - Mangano, Silvina (2017)
Root hair polar growth is endogenously controlled by auxin and sustained by oscillating levels of reactive oxygen species (ROS). These cells extend several hundred-fold their original size toward signals important for plant survival. Although their final cell size is of fundamental importance, the molecular mechanisms that control it remain largely unknown. Here we show that ROS production is controlled by the transcription factor RSL4, which in turn is transcriptionally regulated by auxin through several auxin response factors (ARFs). In this manner, auxin controls ROS-mediated polar growth by activating RSL4, which then up-regulates the expression of genes encoding NADPH oxidases (also known as RESPIRATORY BURST OXIDASE HOMOLOG proteins) and class III peroxidases, which catalyze ROS production. Chemical or genetic interference with ROS balance or peroxidase activity affects root hair final cell size. Overall, our findings establish amolecular link between auxin and ROS-mediated polar root hair growth.